The Application of Restorative Justice to Criminal Acts Committed by Persons with Disabilities in The Perspective of Educational Criminalization (Case Study in Semarang) - Alya Lutfianti; Indah Sri Utari (Universitas Negeri Semarang, 2025)
Persons with disabilities facing the law need special legal protections to ensure equal and non-discriminatory justice. However, in law enforcement practice in Indonesia, the implementation of proper accommodation and legal assistance is still not optimal. This research aims to analyze legal protection for persons with disabilities and the application of restorative justice in the perspective of educational criminalization. The research method used is normative research with a legislative and conceptual approach. The results of the study show that even though legal regulations are available, they still face obstacles in their implementation, so that the application of restorative justice based on educational criminalization is seen as more humane and just because it focuses on recovery and rehabilitation.